Al-Hilal’s victory over Manchester City: an analysis of Western media representations of the event and its symbolic connotations - Al-Sheddi, Mona Mohammed Ibrahim (Journal of Humanities & Social Sciences, 2025)
Al-Hilal’s victory over Manchester City in the 2025 FIFA Club World Cup was an unprecedented sporting event that attracted wide attention from Western media. This study analyzed how this victory was represented in Western coverage, approaching it as a symbolic moment laden with meanings that transcend the sporting context, in order to understand its reception within global media discourse. A qualitative analytical approach was employed through content analysis of articles published in leading Western outlets during the first week after the match, aiming to uncover discursive framings and representational patterns. The analysis revealed four main themes: downplaying the importance of the victory, framing the event as an unexpected surprise, reproducing Eurocentric perspectives in the narrative, and adopting a cautious and controlled approach to its broader implications. These findings show that the event was not ignored, but was at times stripped of its symbolic significance—either through questioning its meaning or confining it to the frame of a fleeting shock. The findings from this sample of Western media coverage indicate a variation between celebratory and cautious tones, with early signs of a relative shift in representing the Saudi football project—from being portrayed merely as financial investment to being recognized as a serious competitive project—alongside a relative decline in the prevalence of the usual negative discourse. Based on these results, the study recommends strengthening international communication and media strategies to highlight Saudi sporting achievements, with emphasis on constructing alternative narratives that transcend entrenched stereotypes in Western discourse, and encouraging future comparative studies to assess the impact of such events on perceptions of the Kingdom’s image and its global football standing.